Стратегічне управління земельними ресурсами в умовах воєнного стану: виклики, інновації та перспективи повоєнного відновлення - Рябова, Юлія Петрівна (НУБіП України, 2025)
Abstract. Ukraine’s land resources have undergone significant changes under martial law, impacting land management, usage, and legal regulation. Challenges include infrastructure destruction, environmental threats from pollution and landmines, loss of documentation, and shifts in land use due to population displacement. Recovery requires a strategic approach, the implementation of innovations, cadastral digitization, and international support. Special attention should be given to the agricultural sector, environmental safety, and legislative modernization for sustainable development and national security
Strategic land resource management under martial law: challenges, innovations, and post-war recovery prospects
Keywords: управління земельними ресурсами; екологія; кадастри; land management; ecology; cadastres